The effect of exposure frequency on incidental vocabulary acquisition - Heidari-Shahreza, Mohammad Ali; Moinzadeh, Ahmad; Barati, Hossein (Penerbit UKM, 2014)
This study explored the effect of incidental vocabulary exposure on receptive and productive vocabulary knowledge, acquisition and retention among 90 Iranian EFL learners. The research focused on how exposure frequency or the number of encounters with the target words in reading passages affected different aspects of vocabulary knowledge such as receptive and productive knowledge of orthography, parts of speech, associations and meaning. In general, the findings (based on ANOVA and its non-parametric version, Kruskal-Wallis whenever normality requirement was not met) indicated that incidental exposure to second language (L2) words through reading passages might be conducive to vocabulary acquisition and retention. Particularly, it was revealed that as the number of encounters to L2 target words increased, the learners were more successful in acquiring different aspects of vocabulary knowledge. In this regard, the effect of exposure frequency was significant in both the immediate and delayed post-test for all aspects of vocabulary knowledge when the amount of exposure increased from one encounter to seven. Nevertheless, the analyses of the scores obtained from the seven subtests suggested that the effect of exposure frequency may vary for different aspects of vocabulary knowledge. Moreover, there was no marked distinction between receptive and productive aspects of vocabulary knowledge. However, the scores on the semantic subtests revealed that increasing the number of exposure frequency could mostly affect the receptive knowledge of meaning and form as well as productive knowledge of associations. These aspects were also more vulnerable with the passing of time. It is recommended that English teachers put incidental vocabulary acquisition within the perspective of a longitudinal, intensive and systematic vocabulary recycling where the learners' knowledge of vocabulary is reinforced and accumulated over time. Moreover, English teachers may make use of form-focused or explicit instruction to compensate for any lack of time or their learners' need for more incidental exposure to L2 vocabulary.